Differential Profile of Cytokine TNF-Α, MDA and SOD Level in Sepsis Induced By Cecal Ligation and Puncture Compared with Induced By LPS - Dian Samudra (Journal of Global Pharma Technology, 2019)
Objective: The aim of this study is to analyse the differential of TNF-α cytokine profile, MDA, and SOD levels between sepsis-induced in mice by cecal ligation and puncture (CLP) which were then compared with lipopolysaccharide (LPS) injection. Methods: This study made use of experimental animals, 28 mice divided into 4 groups: control (healthy mice), mice model of sepsis due to cecal ligation and puncture (CLP), a group of mice modeled sepsis due to LPS i.p injection of 103 (LPS1) and LPS 105 CFU i.p injection dose (LPS2). Afterward, TNF-α levels were examined using a sandwich enzyme immunoassay technique and calculation of MDA and SOD levels in blood, liver, and kidneys. Results: The results showed that the level of TNF-α cytokines in mice model of sepsis with LPS induction of 105 CFU (LPS2) increased significantly (p <0.05) compared to the sepsis model with CLP (LPS2: 1.11 ng/ml vs 0.34 ng/ml). MDA levels in serums, livers, and kidneys of the experimental animals were also found to increase after LPS induction of 103 and 105 CFU doses. In contrast, SOD levels experienced a significant decrease due to LPS injection of dose 105 CFU in comparison with the CLP sepsis model. Conclusion: This study found that the best sepsis model was the one with LPS induction of 105 CFU doses which was characterized by a high production of TNFα cytokines, excessive MDA levels, and low levels of SOD antioxidant enzymes. By finding the best sepsis model, it can be used for therapeutic needs by targeting the inhibition of TNF-α proinflammatory cytokines and oxidative stress indicators MDA and SOD. Keywords: cecal ligation and puncture (CLP), LPS, MDA, sepsis, SOD, TNF-α